Pembuatan Asset Creation Untuk Content Instagram Pixli Studio - Candra Paramita, Luh Putu Diah; Ngurah Wirawan, I Gusti; Rini Astuti, Ni Ketut (Program Studi Desain Komunikasi Visual, 2024)
This article discusses the author's experience during an internship at Pixli Studio, a company in the creative industry specializing in animation, illustration, and graphic design. The internship, which took place from February 19 to June 17, 2024, aimed to deepen understanding and practical skills in asset creation for Instagram content. The asset creation process includes several stages: sketching, outlining, and coloring, all done using Clip Studio Paint software. Pixli Studio, founded in 2021 by I Gede William Sedana Putra, offers various creative services including animation, story and visual development, and graphic design. During the internship, the author was directly involved in the creation of visual assets such as characters and backgrounds, designed for promotional content on the studio's Instagram. The methods used in the internship included observation, interviews, and documentation. Observations were made through direct monitoring at the studio, interviews with the CEO and team, and documentation of the work process as reference material. The outcome of the internship was various visual assets used for promotional content on Pixli Studio's Instagram, which underwent periodic evaluation to ensure quality and alignment with the studio's branding. This internship experience provided the author with significant insights and practical skills in the field of visual communication design, particularly in asset creation and creative studio management. Additionally, the internship strengthened the collaboration between academia and the creative industry, benefiting students, universities, and industry partners.